2011
DOI: 10.1100/tsw.2011.132
|View full text |Cite
|
Sign up to set email alerts
|

The Inter-Relationship of Periostin, TGFβ, and BMP in Heart Valve Development and Valvular Heart Diseases

Abstract: Recent studies have suggested an important role for periostin and transforming growth factor beta (TGFβ) and bone morphogenetic protein (BMP) ligands in heart valve formation and valvular heart diseases. The function of these molecules in cardiovascular development has previously been individually reviewed, but their association has not been thoroughly examined. Here, we summarize the current understanding of the association between periostin and TGFβ and BMP ligands, and discuss the implications of this assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 128 publications
(195 reference statements)
2
39
0
Order By: Relevance
“…The increase in the expression of POSTN in CRS, with and without polyps, tissue is not surprising because POSTN plays multiple potential roles in epithelial structure and immune regulation. Several lines of evidence have suggested the importance of this matricellular protein in accelerating lung inflammation by enhancing chemokine production in fibroblasts, eosinophil recruitment, or TGF-beta activation in airway epithelial cells (Wen et al, 2010;Conway et al, 2011). What turned out to be more interesting in our analysis was that POSTN expression was greater in CRSwNP than CRSsNP, and especially that similar results were obtained by Zhang et al in previous studies (Zhang et al, 2012).…”
Section: Discussionsupporting
confidence: 86%
“…The increase in the expression of POSTN in CRS, with and without polyps, tissue is not surprising because POSTN plays multiple potential roles in epithelial structure and immune regulation. Several lines of evidence have suggested the importance of this matricellular protein in accelerating lung inflammation by enhancing chemokine production in fibroblasts, eosinophil recruitment, or TGF-beta activation in airway epithelial cells (Wen et al, 2010;Conway et al, 2011). What turned out to be more interesting in our analysis was that POSTN expression was greater in CRSwNP than CRSsNP, and especially that similar results were obtained by Zhang et al in previous studies (Zhang et al, 2012).…”
Section: Discussionsupporting
confidence: 86%
“…Importantly, excess accumulation of collagen in both ascending and descending aortic tissues of Fbn1 +/C1039G mice, as seen by us and others, is speculated to be able to interfere with collagen fiber orientation and alignment. Other workers have shown that exogenously added TGFβ1 increases the levels of periostin, which is required for collagen assembly and organization (Snider et al 2008;Conway et al 2011). The exact role of TGFβ1 and other TGFβ ligands (i.e., TGFβ2, TGFβ3) in collagen organization in vivo in the aortic tissue of Fbn1 +/C1039G mice remains to be studied.…”
Section: Discussionmentioning
confidence: 97%
“…Similarly to TGF-β, BMPs have been investigated during development and emerged as key factors in heart valve formation and morphogenesis [30,31]. BMP4 is important for the local proliferation and migration of cardiac neural crest cells and so for outflow tract valve development [32,33].…”
Section: Bone Morphogenetic Proteinsmentioning
confidence: 99%